(untitled) (The Spectrum, 2025)
This paper explores Amitav Ghosh’s Countdown (1999) and foregrounds his reactions to the testing of nuclear weapons in India on 11th May 1998, followed instantly by the Pakistani tests. The travelogue follows the extraordinary journeys of Ghosh to search for people’s impression about the tests. He is apprehensive about the complexities of the nuclear issues and interconnectedness of the fate of both India and Pakistan. He forewarns that the tests will engender fatal consequences and give rise not only to geo-political tension between the two neighbouring countries but also precipitate horrendous and hair-raising disaster on humans, environment and the world itself. He prognosticates impending dooms lurking around in the world on the brink of environmental ruination, human genocide, and ravages of human civilization. Nuclear test, for Ghosh, is a symbol of mutually assured destruction, and therefore, he appeals for addressing the crises to be caused by the testing of nuclear devices. The objective of this paper is to gauge the trepidation and insidious effects of nuclear proliferation, and to unmask the hidden motives behind the nuclear tests. The research is effectuated by means of close textual analysis of the text.